Outcomes at 18 mo of 37 noma (cancrum oris) cases surgically treated at the Noma Children's Hospital, Sokoto, Nigeria. (12th August 2020) - Farley, Elise S; Amirtharajah, Mohana; Winters, Ryan D; Taiwo, Abdurrazaq O; Oyemakinde, Modupe J; Fotso, Adolphe; Torhee, Linda A; Mehta, Ushma C; Bil, Karla A; Lenglet, Annick D
Abstract: Background: Noma is a rapidly progressing infection of the oral cavity frequently resulting in severe facial disfigurement. We present a case series of noma patients surgically treated in northwest Nigeria. Methods: A retrospective analysis of routinely collected data (demographics, diagnosis and surgical procedures undergone) and in-person follow-up assessments (anthropometry, mouth opening and quality of life measurements) were conducted with patients who had surgery >6 mo prior to data collection. Results: Of the 37 patients included, 21 (56.8%) were male and 22 (62.9%) were aged >6 y. The median number of months between last surgery and follow-up was 18 (IQR 13, 25) mo. At admission, the most severely affected anatomical area was the outer cheek (n = 9; 36.0% of patients had lost between 26% and 50%). The most frequent surgical procedures were the deltopectoral flap (n = 16; 43.2%) and trismus release (n = 12; 32.4%). For the eight trismus-release patients where mouth opening was documented at admission, all had a mouth opening of 0–20 mm at follow-up. All patients reported that the surgery had improved their quality of life. Conclusions: Following their last surgical intervention, noma patients do experience some improvements in their quality of life, but debilitating long-term sequelae persist.